On the nature of conspicuous consumption : linking evolution, american old institutionalism and methodological issues - Pezzini, Lukas Reiter (2020)
In this paper we aim to propose a dialogue between the work of main exponents of what is known as American Old Institutionalism (AOI); Walton Hamilton (1919), Thorstein Veblen (1898, 1899), and the writings of Geoffrey Hogdson (1998; 2004; 2010), Ulrich Witt (2008; 2010; 2011; 2013), Wolfhard Kaus (2013) and Karin Knottenbauer (2010). It is argued what unites all these authors is the search for evolutionary traits of economic behavior. The case is made for the category of conspicuous consumption and its evolutionary roots. To do so, we first present the reader with a brief of what is the essence of the American Old Institutionalism (AOI) and the propositions of Hamilton (1919) for an economic theory that would embrace dynamics instead of statics. Then, an exhibition of Veblen’s (1899) conspicuous consumption theory is offered, making it possible for the future linkage between evolutionary features and the topic of conspicuity. The paper proceeds with an appeal for modern evolutionary economists to pay more attention to the matter of ontology and epistemology when approaching the topic of consumption in Economics. Here the work of Campbell (1993) and Buss (2008) come handy to clarify the underpinnings of the act of conspicuous consumption, its emulative behavior and the eventual consumption novelty. Within that stylized approach, our conclusions show that evolutionary economics still has not offered a robust framework when dealing with key economic categories such as conspicuous consumption. Also, the lack of linked explanatory categories is at the core of the ontological and epistemological issues the theory faces nowadays. Keywords Evolution • Evolutionary